Linking results-based aid and capacity development support: conceptual and practical challenges - Niels Keijzer; Heiner Janus (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The most recent addition to the development cooperation toolbox is results-based aid (RBA), a development cooperation modality that disburses grants or loans in response to the achievement of pre-defined results. There are ongoing experiments in the use of RBA, as well as ongoing research efforts to determine under what conditions and circumstances it can be effective. An underexplored question is how RBA interventions relate to capacity development support (CDS) on conceptual and practical levels. This question is important because “capacity gaps” are frequently put forward by donors as a justification for external CDS. Therefore, how does the introduction of RBA interact with CDS within the broader portfolio of aid modalities? And what are the potential challenges and implications? All aid modalities include capacity development considerations, yet RBA specifically assumes a “hands-off” approach on the side of the donor and leaves it to partner countries to determine capacity development needs and priorities. At the same time, there can be potential for promoting complementarities between RBA and CDS. Both aim to achieve sustainable development outcomes and improve broader institutional performance beyond the specific intervention. Emerging evidence suggests that there is potential for a conscious link between RBA and CDS interventions, for which different options are assessed in this paper. All options would benefit from strong investments in the design of interventions, as well as space for adapting interventions in response to ongoing changes in local contexts.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Wirksamkeit und Evaluierung